2017
DOI: 10.5489/cuaj.4631
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening among family physicians in Ontario: An update on attitudes and current practice

Abstract: Introduction: This study serves as an update of prostate cancer screening practices among family physicians in Ontario, Canada. Since this population was first surveyed in 2010, the Canadian Task Force on Preventive Health Care (CTFPHC) and the United States Preventive Services Task Force (USPSTF) released recommendations against prostate cancer screening. Methods: An online survey was developed through input from urologists and family practitioners. It was distributed via email to all members of the Ontario M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…An example of the positive impact of guidelines in reducing overuse has been with prostate cancer screening. [72] Conversely, clinicians may order tests that are not clinically indicated because policies mandate it. [29] Guidelines are considered a reputable source of evidence based recommendations to support clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of the positive impact of guidelines in reducing overuse has been with prostate cancer screening. [72] Conversely, clinicians may order tests that are not clinically indicated because policies mandate it. [29] Guidelines are considered a reputable source of evidence based recommendations to support clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretations and attitudes toward guidelines, protocols and policies were found to signi cantly in uence test ordering behaviour in 21 articles. Akerman et al [72] found that that there was a drop in prostate screening rates from 91.7-80.4% when new recommendations from the Canadian and United States Preventive Services Task Force were released following evidence of little net bene t from screening. A number of studies showed that non-existent or discordant guidelines can result in overtesting.…”
Section: Guidelines Protocols and Policiesmentioning
confidence: 99%
“…But how must I say "you have to accept it" if the neurologist says that perhaps the patient should be looked at by someone else" [46] "If I get a letter from the diagnostic centre with the comment "You request 10% more than the average GP in Maastricht", then you get critical. You wonder if we should wait a bit longer with this patient" [46] "If you're not going to order it, the next doctor will" [59] "Environment/context factors" affecting clinician test ordering behaviour, with number of articles and quotes from [33,36,37,45,47,49,50,[53][54][55][56][57][58][59][60]62,64,66,72,73,87] "There are situations where I've ordered an echo when I otherwise would not have because guidelines mandated" [37] "I think there's more, as much as we've developed these decision rules-I think there's a lot to be said about just experience" [47] "I think people are wary of practicing not in line with that and then they have potential then for criticism" [60] "There's plenty of guidelines, but they're all different and there's nothing official...there's no hard and fast rule" [60] "Because I work in a teaching practice, my residents are very devoted to guidelines. A lot of them are driven by the more recent guidelines" [66] ancial ives and hip of tests 21 articles [1,2,7,15,21,23,[36][37][38]…”
Section: Discussionmentioning
confidence: 99%
“…Interpretations and attitudes toward guidelines, protocols and policies were found to signi cantly in uence test ordering behaviour in 21 articles. Akerman et al [54] found that that there was a drop in prostate screening rates from 91.7% to 80.4% when new recommendations from the Canadian and United States Preventive Services Task Force were released following evidence of little net bene t from screening. A number of studies showed that non-existent or discordant guidelines can result in overtesting.…”
Section: Guidelines Protocols and Policiesmentioning
confidence: 99%